FOREIGN EXPERIENCE OF DIGITAL ECONOMY DEVELOPMENT STRATEGIES - Sotvoldiyev Alisher Abdumuxtarovich (Scholar Express Journals, 2024)
In this article are discribed the development of the digital economy in the world, the advantages and disadvantages of digitalization, highlights the problems and limitations that impede the full construction of the digital economy of the Republic of Uzbekistan, and also identifies promising directions for its development
Keywords: digitalization; digital economy; economic development; globalization